Meta-transcriptomic analysis reveals the geographical expansion of known sugarbeet-infecting viruses and the occurrence of a novel virus in sugarbeet in the United States - Chinnadurai, Chinnaraja; Wyatt, Nathan A.; Weiland, John J.; Neher, Oliver T.; Hastings, Joe; Bloomquist, Mark W.; Chu, Chenggen; Chanda, Ashok K.; Khan, Mohamed; Bolton, Melvin D.; Ramachandran, Vanitharani (Frontiers in Plant Science, 2024)
In this study, meta-transcriptome sequencing was conducted on a total of 18 sugarbeet (Beta vulgaris L. subsp. vulgaris) sample libraries to profile the virome of field-grown sugarbeet to identify the occurrence and distribution of known and potentially new viruses from five different states in the United States. Sugarbeet roots with symptoms resembling of rhizomania caused by beet necrotic yellow vein virus (BNYVV), or leaves exhibiting leaf-curling, yellowing to browning, or green mosaic were collected from the sugarbeet growing area of California, Colorado, Idaho, Minnesota, and North Dakota. In silico analysis of de novo assembled contigs revealed the presence of nearly full-length genomes of BNYVV, beet soil-borne virus (BSBV), and beet soil-borne mosaic virus (BSBMV), which represent known sugarbeet-infecting viruses. Among those, BNYVV was widespread across the locations, whereas BSBV was prevalent in Minnesota and Idaho, and BSBMV only detected in Minnesota. In addition, two recently reported Beta vulgaris satellite virus isoforms (BvSatV-1A and BvSatV-1B) were detected in new locations, indicating the geographical expansion of this known virus. Besides these known sugarbeet-infecting viruses, bioinformatic analysis identified the widespread occurrence of a new uncharacterized Erysiphe necator-associated abispo virus (En_abispoV), a mycovirus-related virus that was identified in all 14 libraries. En_abispoV contains two RNA components, and the near complete sequence of both RNA1 and RNA2 were obtained from RNASeq and were further confirmed by primer-walking RT-PCR and Sanger sequencing. Phylogenetic comparison of En_abispoV isolates obtained in this study showed varying levels of genetic diversity within RNA1 and RNA2 to the previously reported isolates. The undertaken meta-transcriptomic approach revealed widespread nature of coexisting viruses associated with field-grown sugarbeet exhibiting virus disease-like symptoms in the United States.